(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the impact of creative writing exercises on language proficiency and self-expression in second language (L2) learners. Integration of creative tasks such as short stories, poems and song lyrics, the study aims to investigate how these activities affect vocabulary acquisition, grammar use and general language skills.